Protein C Deficiency in Two Austrian Families - Pabinger-Fasching, I; Bertina, R M; Lechner, K; Niessner, H; Korninger, Ch (Thrombosis and Haemostasis, 1983)
Protein C antigen was determined by Laurell rocket immunelectrophoresis in 225 patients with a history of venous thrombosis. Among these patients two females with protein C deficiency were detected. Additional studies in the families of the protein C deficient patients revealed further 7 family members with protein C deficiency. In 8 not anticoagulated patients with protein C deficiency the protein C ranged from 36 to 62% (median: 45%). In one patient on oral anticoagulant treatment protein C antigen concentration was < 10%, FII and F X were 65 and 50%, respectively. The pattern of inheritance was consistent with autosomal dominant inheritance. 5 of the 9 protein C deficient patients had severe thrombotic tendency characterized by recurrent deep venous thrombosis (n = 4), pulmonary embolism (n = 1), probable mesenteric vein thrombosis (n = 1) and superficial thrombophlebitis (n = 2). All protein C deficient patients without thrombosis were less than 17 years old.
Keywords: Protein C deficiency; Thrombotic disease